Epidemiology and factors associated with the perioperative course of patients undergoing hip fracture during the initial phase of the state of emergency declared in 2020 - Santander, S.; Lanuza, A.; Longás, J.; Úbeda, F.; Marco, C.; Luesma, M. J. (Frontiers in Medicine, 2025)
IntroductionCurrently, there is no gold standard anesthetic plan for elderly patients with hip fractures who must undergo surgery. The state of alarm during 2020 due to the COVID-19 pandemic changed certain hospital paradigms, prompting an investigation into differences in anesthetic management and patient survival for hip fracture surgeries using gamma nail osteosynthesis in 2020 compared to 2019.Materials and methodsA historical cohort study was conducted to assess morbidity and mortality, with data obtained from anonymized medical records.ResultsStatistically significant differences were found, notably an increase in Body Mass Index during confinement. A statistically significant decrease in leukocyte and hemoglobin levels was observed after surgery. However, there were no statistically significant differences in mortality between 2019 and 2020. Patients who did not require vasoactive drugs during surgery to maintain blood pressure levels above 90/60 mmHg had a better survival rate.ConclusionDespite the reduction in postoperative hospital surveillance time, no increase in complications was found. This allowed for early patient reintegration into daily life, early functional rehabilitation, and the minimization of economic costs.